Effects of Altering Mitochondrial Antioxidant Capacity on Molecular and Phenotypic Drivers of Fibrocalcific Aortic Valve Stenosis - Roos, Carolyn M.; Zhang, Bin; Hagler, Michael A.; Verzosa, Grace C.; Huang, Runqing; Oehler, Elise A.; Arghami, Arman; Miller, Jordan D. (Frontiers in Cardiovascular Medicine, 2021)
kground: While a small number of studies suggest oxidative stress has an influential role in fibrocalcific aortic valve disease (FCAVD), the roles of specific antioxidant enzymes in progression of this disease remain poorly understood. Here, we focused on selectively altering mitochondrial-derived oxidative stress—which has been shown to alter progression of a myriad of age-associated diseases—on the progression of molecular and phenotypic drivers of FCAVD. Methods: We generated low density lipoprotein receptor-deficient, Apolipoprotein B100-only mice (LA) that were either hapolinsufficient for MnSOD (LA-MnSOD+/-) or genetically overexpressing MnSOD (LA-MnSODTg/0). After 6 months of Western diet feeding, mice underwent echocardiography to assess valvular and cardiac function and tissues were harvested. Quantitative-RT PCR, immunohistochemistry, and histopathology were used to measure changes in molecular pathways related to oxidative stress, calcification, and fibrosis. Results: While reductions in MnSOD increased oxidative stress, there was not an overt phenotypic effect of MnSOD deficiency on valvular and cardiac function in LA-MnSOD+/- mice. While markers of canonical bone morphogenetic protein signaling tended to increase in valve tissue from LA-MnSOD+/- (e.g., p-SMAD1/5/8 and osterix), we did not observe statistically significant increases in osteogenic signaling. We did, however, observe highly significant reductions in expression of osteopontin, which were associated with significant increases in calcium burden in LA-MnSOD+/- mice. Reciprocally, genetically increasing MnSOD did not preserve valve function in LA-MnSODTg/0, but we did observe slight reductions in p-SMAD1/5/8 levels compared to their non-transgenic littermates. Interestingly, overexpression of MnSOD dramatically increased expression of osteopontin in valve tissue from LA-MnSODTg/0 mice, but was not sufficient to attenuate calcium burden when compared to their LA-MnSOD0/0 littermates. Conclusions: Collectively, this study demonstrates that maintenance of mitochondrial antioxidant capacity is important in preventing accelerated disease progression in a mouse model of FCAVD, but that effectively altering mitochondrial antioxidant capacity as a monotherapeutic approach to slow key histopathological and molecular drivers of FCAVD remains biologically and therapeutically challenging.